Visualization of Material Using Concept Map as a Strategy in Design of Learning Material for Nihon Bunka Shakai Nyumon Subject - Rahayu Rismawati Nur Rahman; Ardietyo Hartoro; Ari Artadi; Hari Setiawan (Universitas Diponegoro, 2021)
This research examined the application of a concept map in designing learning material to help students understand by visualizing information of various topics that covers the social, cultural, and economic topics included in the Nihon Bunka Shakai Nyumon Subject. Manifesting Ausubel subsumption theory, three of Model Kemp. variables such as content sequencing, task analysis, and instructional delivery methods accompanied by the use of audio-visual media were conducted to construct the learning design and strategy of Japanese society and culture that are valid, effective, and encourage critical thinking of the students. The trials of learning material, strategy, and evaluation had been implemented in Nihon Bunka Shakai Nyumon subject at the odd semester of 2020-2021 academic year based on the 2017 curriculum of Japanese Language and Culture Department, Darma Persada University. As the result, about 48% of students stated their satisfaction with the implementation of the Nihon Bunka Shakai Nyumon subject and about 31% of the students conveyed that they got a significant increase in knowledge about Japanese society and culture.